The Attractiveness of the Baltic Countries as a Sales Market: Evidence for Beauty Industry - Ambrozie, Alisa-Mihaela; Topliceanu, Stefan-Catalin; Sorcaru, Sergiu; Pirju, Sergiu-Ionel (Acta Universitatis Danubius. Œconomica, 2021)
Shai Tech is a Romanian company, which commercializes its personal care products in the United States through its online store. The company wants to expand in Europe, first in one of the Baltic countries. The aim of this paper is to study how a beauty company like Shai Tech evaluates the attractiveness of countries and target markets when it decides to sell its products in foreign markets. In order to achieve this purpose, the attractiveness of the Baltic countries from the perspective of demographic, economic, and labor market, also target market characteristics will be compared. The applied methodology involves 30 variables from the three dimensions analyzed and the awarding of scores for the three Baltic countries. The results reveal that Lithuania is best positioned in both the demographic dimension and economic and labor market aspects. In addition, Lithuania and Estonia have similar scores regarding the target market indicators.